Cannabidiol and nano-selenium mediate intestinal barrier function by affecting mucosal microstructures, and gut-associated immunological and oxidative stress response in the gut of chickens infected with C. perfringens - Szkopek, Dominika; Mendel, Marta; Kinsner, Misza; Ognik, Katarzyna; Szyryńska, Natalia; Lewczuk, Bogdan; Kozłowski, Krzysztof; Kos, Ivica; Konieczka, Paweł (Frontiers in Immunology, 2025)
Nutritional additives with biological activity, such as cannabidiol (CBD) and nano-selenium (nano-Se), are viable to prevent bacterial diseases such as necrotic enteritis in chickens. The present study hypothesized that CBD and nano-Se mediate epigenetic and oxidative DNA changes in blood and intestinal epithelial cells and can affect intestinal development and functionality in broiler chickens at an early stage of infection with C. perfringens. This study revealed that both compounds, in combination under physiological or pathophysiological conditions, can act synergistically, improving the indices of histomorphometry of duodenum, jejunum, and ileum. Examination of the structures and ultrastructures of the gastrointestinal tract showed that CBD + nano-Se supplementation did not manifest adverse effects on the host gut indices. In contrast, epigenetic and oxidative markers of blood and gut structures indicated that these components balanced the immune system, mitigating the excessive inflammatory response caused by infection, which boosted the immune response of birds to challenge. There were also significant correlations between indicators of intestinal barrier function, such as diamine oxidase and lactic acid levels, and histomorphometry and markers of DNA integrity in the blood and intestine of chickens. In addition, it was shown that nano-Se increased hemoglobin concentration, which may be beneficial in the host's response to pathogen stimuli. These findings evidenced the health-promoting effect of cannabidiol and nano-selenium in C. perfringens-infected chickens and provided new insights into the mechanism of action of both nutritional additives.